Examine the Effect of Social Factors on Information Technology Acceptance in Accounting profession by Using TAM Model (Global Journal of Management and Business Research, 2012)
Nowadays, Information technology (IT) is considered as a very important and most useful part of industry, economic and culture, accounting is the system of recording and summarizing business which provide the users with information in their decision making process this research tries to examine the effect of social factors on IT acceptance to by using TAM model. The research method is descriptivesurvey based on which the author used descriptive and deductive statistic to meet the research goals. The results Keywords : system usage, Perceived usefulness, Perceived ease use, information technology, Social factors and accounting profession. indicate the lack of perceived ease of use among ease accountants.
Keywords: system usage; Perceived usefulness; Perceived ease use; information technology; Social factors and accounting profession